IMPLEMENTASI FUNGSI MANAJEMEN DALAM TATA KELOLA KURIKULUM DI SEKOLAH - Herawati, Endang Sri Budi; Supriyana, Heri (LPPM UNU CIREBON, 2024)
This research aims to describe the application of management functions in curriculum management at the senior secondary school level in Sleman Regencies, namely: (1) curriculum planning; (2) organization and implementation of the curriculum; (3) curriculum evaluation; and (4) curriculum development. The research method used is a qualitative method with inductive descriptive data analysis techniques and source triangulation to check the validity of the data. Data collection was carried out using observation techniques, in-depth interviews, and examining relevant documents. The research results provide an illustration that the application of management functions in curriculum governance will provide good results for the quality of education and learning. The governance is: (1) curriculum planning begins with a needs analysis and efforts to fulfill the needs of students both by the school in the form of an education unit level curriculum, and by teachers in the form of lesson plans/teaching modules; (2) the organization and implementation of the curriculum is carried out by distributing tasks and responsibilities to teachers and school staff, providing clear directions to students and teachers, facilitating learning activities, and creating an environment that is conducive to learning; (3) curriculum evaluation, involving regular monitoring and evaluation to ensure that the curriculum runs as planned; and (4) curriculum development, which is an ongoing process to ensure that the curriculum remains relevant, effective, and in line with student needs and educational developments.